DEVELOPMENT OF ECTA-T AND EMIS-T WITH A COMBINATION OF THREE-TIER AND CERTAINTY RESPONSE INDEX METHODS IN ENVIRONMENTAL CONCEPT - Rizkiyah, Fitri Rizkiyah (Universitas Cokroaminoto Palopo, 2026)
Environmental pollution is a problem that often occurs in the environment where we live, and requires the ability to think creatively to be able to solve it. The ability to think creatively in solving environmental problems is determined by their knowledge related to ecology. Therefore this study aims to create an instrument that can measure students' misconceptions (EMis-T) in ecological material and an instrument that can measure students' creative thinking skills (ECTA-T) in solving environmental problems. The research was conducted with reference to the Research and Development (R&D) method with the Borg & Gall (2003) development model which was modified into four development steps, including: (1) Preliminary study stage; (2) Development stage; (3) validation and trial stage; (4) Application Stage. The type of instrument developed is in the form of an essay type written test by combining the three tier test type and certainty response index. The objects that were used as targets for the development of this instrument were class X senior high school. Based on the results of the analysis it is known that the product that has been developed has valid criteria, medium high reliable value, no discriminating power which has a negative value, and questions that have an easy level of difficulty do not dominate, so this product can be used by educators to measure creative thinking skills and students' misconceptions about environmental material. The identified level of students' creative thinking ability was dominated by students in the high category. While the level of students' misconceptions that were identified were dominated by students in the low category.